2006
DOI: 10.1146/annurev.psych.56.091103.070258
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Goal Structure, Student Motivation, and Academic Achievement

Abstract: Over the past 25 years, achievement goal theory has emerged as one of the most prominent theories of achievement motivation. This chapter uses an achievement goal framework to examine the influence of classroom and school environments on students' academic motivation and achievement. Considerable evidence suggests that elementary and secondary students show the most positive motivation and learning patterns when their school settings emphasize mastery, understanding, and improving skills and knowledge. Whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
712
3
122

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 975 publications
(869 citation statements)
references
References 64 publications
32
712
3
122
Order By: Relevance
“…Students tend to adopt achievement goals that are consistent in focus to the goals emphasized in their learning environment (Ames & Archer, 1988;Meece, Anderman, & Anderman, 2006). The characteristics of the learning environment and the messages that students subjectively perceive in it are stronger determinants of their motivation, affect, and behavior than the actual characteristics of the learning environment (Ames, 1992;Roeser & Eccles, 1998).…”
Section: Perceived Social-psychological Contexts On Achievement Goalsmentioning
confidence: 99%
“…Students tend to adopt achievement goals that are consistent in focus to the goals emphasized in their learning environment (Ames & Archer, 1988;Meece, Anderman, & Anderman, 2006). The characteristics of the learning environment and the messages that students subjectively perceive in it are stronger determinants of their motivation, affect, and behavior than the actual characteristics of the learning environment (Ames, 1992;Roeser & Eccles, 1998).…”
Section: Perceived Social-psychological Contexts On Achievement Goalsmentioning
confidence: 99%
“…Our findings of the role of goal structures on students' own social goals builds upon the important work conducted by Shim et al (2013), and adds to the literature in several ways: a) we examined three types of classroom goals (e.g., Midgley et al, 2000) rather than two, b) we focused on high school students rather than middle school students, and c) we expanded empirical support for goal structures through examining how goal structures (and changes in goal structures) predicted trajectories of social goals rather than just mean levels. Our results suggest that classrooms should emphasize academic mastery goals and de-emphasize performance-avoidance goals (see Meece, Anderman, & Anderman, 2006 for recommendations) to encourage the development of adaptive social goals.…”
Section: The Role Of the School Contextmentioning
confidence: 95%
“…Eccles and colleagues (Eccles & Midgley, 1989;Eccles et al, 1993;Meece et al, 2006) have argued that the decline in motivation and self-beliefs often seen at the time of transition is a consequence of the mismatch between needs and environment (stage-environment fit). Many of the changes students encounter in the new school do not facilitate positive developmental outcomes because of their emphasis on competition and social comparison at a time when adolescents are becoming increasingly self-conscious e.g., increased adoption of ability groupings, greater emphasis on, and rewards for, demonstrating normative ability.…”
Section: Development School Transition and Stage-environment Fitmentioning
confidence: 99%
“…The move to secondary school also takes place at a time when significant individual and social developmental changes are occurring (see Eccles & Midgley, 1989;Wigfield, Eccles, & Pintrich, 1996). Given that educational research has generally shown school transitions to coincide with maladaptive changes in perceptions of the self (Meece, Anderman, & Anderman, 2006), it is important to understand the motivational and environmental factors that help to explain declining self-evaluations. The purpose of the present study was to utilize achievement goal theory (Elliot, 1999(Elliot, , 2005 within a stage-environment fit framework (Eccles & Midgley, 1989) to identify developmental change in selfperceptions as young adolescents transition from primary to secondary school.…”
mentioning
confidence: 99%